Aplikasi Modified Method SNI 03-2834-2000 pada Campuran Self Compacting Concrete - Riyan Nehemia Situmorang; Priyanto Saelan (RekaRacana: Jurnal Teknil Sipil, 2021)
ABSTRAKSelf Compacting Concrete ( SCC ) adalah beton yang dapat memadatkan dirinya sendiri tanpa pemadatan eksternal. Kadar pasir pada komposisi campuran SCC harus lebih dari 50% dari agregat gabungan. Perhitungan komposisi campuran SCC belum dilakukan seperti pada perhitungan beton biasa, perhitungan komposisi lebih banyak dilakukan dengan cara trial dan error. Tujuan penelitian ini adalah untuk mengaplikasikan Modified Method SNI 03-2834-2000 pada perancangan campuran SCC, dengan cara mengevaluasi metode lain perancangan campuran SCC, sehingga diketahui apakah cara Modified Method SNI 03-2834-2000 dapat digunakan pada perancangan campuran SCC. Analisis data sekunder dari komposisi bahan serta kaji banding kuat tekan prediksi mengunakan Modified Method SNI 03-2834-2000, dan hasil uji kriteria SCC membuktikan bahwa Modified Method SNI 03-2834-2000 dapat digunakan menjadi salah satu acuan untuk merancang SCC.Kata kunci: self compacting concrete (SCC), modified method SNI 03-2834-2000, komposisi campuran betonABSTRACTSelf Compacting Concrete (SCC) is a type of concrete that can be placed and consolidated under its own weight without any external compaction. The sand content in the SCC mix composition should be more than 50% of the combined aggregate. The calculation of the SCC mix composition is different from ordinary concrete, because its composition calculation is mostly done by trial and error. This research aimed to apply the Modified SNI Method 03-2834-2000 in the SCC mix design. This research was conducted by evaluating the SCC mix design that used other methods. Thus, the effectiveness of the Modified SNI Method 03-2834-2000 for use in the SCC mix design could be identified significantly. In this research, analysis of secondary data from material composition and comparative assessment of predictive compressive strength by utilizing Modified SNI Method 03-2834-2000 had been successfully carried out, and the results of the SCC criteria test indicated that Modified SNI Method 03-2834-2000 is able to be used as  one of the references for designing SCC.Keywords: self compacting concrete (SCC), modified method SNI 03-2834-2000, concrete mixed design